KEUNIKAN DAN KESEHARIAN ANAK AUTISME DI SKHN 02 KOTA SERANG - Silfy Maulidiyah; Yahdinil Firda Nadhirah (STKIP Subang, 2024)
This research was conducted to recognize and understand the uniqueness and daily life of children with special needs (ABK) which focuses on children who have a type of disorder with the brain's nerves or what we often call